2020
DOI: 10.1063/5.0022019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrode gap on radio-frequency discharge characteristics with a hollow electrode

Abstract: In this paper, the effects of electrode gap on the discharge characteristics in low-pressure argon radio frequency (RF) discharge with a hollow electrode were investigated by a two-dimensional particle-in-cell/MCC model. The results show that the time-averaged electric field, electron density, sheath potential drop, and sheath thickness change with the increasing electrode gap. It is also found that the electron density varies non-monotonically with the electrode gap increasing from 4 to 12 mm due to the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…the energy is transferred from ambient turbulence to GAM zonal flows. Similar experimental results have been reported in other devices, such as AUG, DIII-D, JFT-2M, HL-2A and TEXTOR [37][38][39][40][41][42]. On the other hand, figures 6(b) and (d) show that the stretch of the Lissajous cycle is stronger in D plasmas than that in H plasmas, reflecting stronger correlations between GAM zonal flows and ambient turbulence in D plasmas.…”
Section: Interaction Between Gam Zonal Flows and Turbulence In D And ...supporting
confidence: 87%
“…the energy is transferred from ambient turbulence to GAM zonal flows. Similar experimental results have been reported in other devices, such as AUG, DIII-D, JFT-2M, HL-2A and TEXTOR [37][38][39][40][41][42]. On the other hand, figures 6(b) and (d) show that the stretch of the Lissajous cycle is stronger in D plasmas than that in H plasmas, reflecting stronger correlations between GAM zonal flows and ambient turbulence in D plasmas.…”
Section: Interaction Between Gam Zonal Flows and Turbulence In D And ...supporting
confidence: 87%
“…The XOOPIC code is utilized in the simulation, which is an object-oriented 2d3v (two-dimensional coordinate space and three-dimensional velocity space) PIC-MCC code. [32][33][34][35] A detailed description of this model can be found in our previous work, [36] hence in this work the model is described only briefly . Electron and argon ion (Ar + ) are the main particles in the simulation.…”
Section: Description Of Modelmentioning
confidence: 99%
“…[27,41] It has been confirmed that both the sheath oscillation heating and secondary electron heating are important in maintaining the discharges under the simulated conditions in this work. [36] In the following, the variation of the HCE in one RF period is analyzed in detail.…”
Section: Hce Variation Lawmentioning
confidence: 99%
“…The 2D particle-in-cell/Monte Carlo collision (PIC-MCC) simulation of a hollow cathode slot [2] showed that the secondary electron acceleration within the sheath can play an important role. PIC-MCC simulation for HCDs at different electrode gaps [12] showed that a small electrode gap is not beneficial for obtaining large area plasma with high plasma density outside the hole.…”
Section: Introductionmentioning
confidence: 99%